A Modified Method for NADH Stain That is Used to Stain a Muscle Sample From Myopathic Patient - Hasoon, A. H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This  srudy   aimed  to   use  a   new  concentration   from   l\!J3T (Nitroblue tetrazolium) which using NADH   stain ( by used eight different concentrations from (0.2% to 0.06% ).That stain is a mitochondrial and cytoplasmic histochemical stain which gi ves more infom1ation about the metabolic activity of muscle fiber, so it is valuable in determining the types of muscle fibers and good fiber differentiation type {T) and type (TT)  fibers), by reducing NBT in the location of enzyme and gives a blue color in different degrees according to the types of muscle fibers, and we noticed that the concentration 0.1% from NBT gives a good result and different from the concentration 0.2% that was used before. Which meaus that we can use this low concentration fi'om NBT to stain a double samples from patient m uscle samples   by using the same concentration that was used bef'ore .